Vaccine hesitancy in COVID-19 times. An update from Italy before flu season starts - Odone, Anna; Bucci, Daria; Croci, Roberto; Riccò, Matteo; Affanni, Paola; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2020)
The COVID-19 pandemic and response caused a worrying decline in vaccine uptake around the world. In Italy, the immunization coverage targets set in the 2017-19 National Immunization Prevention Plan (PNPV) have been met only partially. The current public health emergency is likely to have negatively impacted on immunization , with the risk of re-occurrence of Vaccine-Preventable Diseases (VPDs) outbreaks. As flu season approaches, both National Health Institutions  and the scientific community in Italy have taken action. Well in advance as compared to previous years, the Ministry of Health released  the Circular to launch the 2020-2021 influenza immunization campaign which this year is longer (starting on October 2020) and extends flu vaccine recommendations to more  “at risk” subgroups, offered the vaccine free of charge. In addition, some Italian Regions have recently tried to make  flu vaccination compulsory for all Healthcare Workers (HCWs). Since 2017, when the law on childhood vaccination in Italy was passed, compulsory vaccination has proved to be a successful strategy towards coverage increase.